Connecting method for Al-Si coating hot forming steel based on laser cladding technology

By adopting laser cladding technology and powder welding in laser wire fill welding technology, the problems of high cost of adjusting the welding wire composition and large heat-affected zone are solved, and efficient and low-cost welding effect is achieved, and the weld performance is matched with the base material.

CN119465140APending Publication Date: 2025-02-18SHANDONG JIANZHU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411845609.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Laser wire fill welding technology has problems such as high cost of adjusting the welding wire composition and large heat-affected zones, which affects welding efficiency and quality.

Method used

采用激光熔覆技术对Al-Si镀层热成形钢进行焊接,使用粉末替代焊丝,通过正交实验设计选取最佳焊接粉末成分,并在焊接过程中设定合适的激光熔覆设备参数。

Benefits of technology

The high tensile strength and hardness of the weld are achieved, the welding cost and heat-affected zone are reduced, and the operationality and economicality of the process are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119465140A_ABST
    Figure CN119465140A_ABST
Patent Text Reader

Abstract

The invention discloses a laser cladding technology-based Al-Si coating hot forming steel connecting method. According to the method, a high-energy laser beam is used for melting materials and welding base metal to form a high-quality welding seam. The laser cladding technology is used for connection of the aluminum-silicon coating hot forming steel plates, the concept that welding wires are replaced with powder is achieved, and compared with the welding wires, the laser cladding technology has the advantages that the powder replacement cost is lower, the welding line grain structure is in a fine isometric crystal shape, the heat affected zone is smaller, experiments are more convenient to conduct, and design components are more diversified. When the laser cladding technology is adopted, the ratio of the delta-ferrite content to the powder is balanced compared with the ratio of the delta-ferrite content to the wire material in a weld joint when the laser filler wire welding technology is adopted, so that a welded joint has good tensile property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a connection method of Al-Si coated hot-formed steel based on laser cladding technology, belonging to the technical field of welding. Background Art

[0002] In recent years, my country's automobile industry has developed rapidly. As a new development direction of automobiles, lightweighting has attracted more and more attention for energy conservation, environmental protection and other issues involved. Among many laser-welded blanks, aluminum-silicon coated hot-formed laser-welded blanks have maximized the advantages of laser wire-filling welding plates and hot stamping processes. Hot-formed steel has great advantages such as high strength, thin thickness, and low manufacturing cost, which perfectly fits the development direction of automobile lightweighting. Therefore, it has been widely used in the automobile manufacturing industry. The ultimate tensile strength after hot stamping can reach more than 1500Mpa, and it is widely used in structural parts such as A-pillars, B-pillars, and door rings of automobiles. Oxidation and decarburization are very likely to occur during its hot stamping process, which affects its usability and safety. Therefore, aluminum-silicon coatings are often prefabricated on the surface of hot-formed steel to isolate the air. The aluminum-silicon coating can maintain excellent antioxidant properties at high temperatures exceeding 900°C. However, during the laser welding process, the aluminum-silicon coating is easily melted into the molten pool, thereby deteriorating the quality and performance of the welded joint. Laser wire welding can metallurgically regulate the composition, structure and properties of the weld joint, greatly improving the quality and performance of the weld joint.

[0003] Although laser wire welding technology has many advantages such as low energy consumption, low cost, high efficiency, diversification, low workpiece assembly gap requirements, and the ability to weld large and thick parts with low power, it still has defects such as high cost of adjusting the welding wire composition and large heat-affected zone. If multiple groups of different welding wire composition experiments or production are carried out, it is necessary to design and order a variety of welding wires with different compositions, which seriously affects the progress and cost.

[0004] In recent years, laser cladding technology (LAM) has been widely used in the field of surface strengthening and repair. Laser cladding uses a high-energy laser beam to melt the cladding material and solidify it on the surface of the parent material to form a cladding layer with high service performance. Laser cladding technology has the characteristics of high efficiency, small heat-affected zone, rapid cooling and solidification, and refined grains. It is the first choice for preparing material surface coatings. Laser cladding technology can also be used for the connection of aluminum-silicon coated hot-formed steel plates. This technology not only retains the original advantages of laser wire welding, but also solves the problems of the latter, such as high cost of adjusting the welding wire composition and large heat-affected zone.

[0005] The present invention proposes to apply laser cladding technology to the connection of Al-Si coated hot-formed steel, realizing the concept of replacing welding wire with powder. Compared with welding wire, it has the advantages of lower powder replacement cost, fine equiaxed grain structure of weld, smaller heat-affected zone, more convenient experiment and more diverse design components. Summary of the invention

[0006] In order to solve the problems of high cost of adjusting the welding wire composition and large heat affected zone in laser wire welding, the present invention uses Al-Si coated hot-formed steel as the base material and welds it using laser cladding technology.

[0007] In order to achieve the above-mentioned purpose, the present invention adopts the following technical solutions:

[0008] A method for connecting Al-Si coated hot-formed steel based on laser cladding technology. The welding powder used is composed of C, Si, Mn, Cr, Mo, B, Ni, and Fe elements, and the mass percentages are: C: 0.03%~0.11%, Si: 0.23%~0.35%, Mn: 1.19%~1.88%, Cr: 0.17%~0.44%, Mo: 0.29%~0.61%, B: 0.0015%~0.0036%, Ni: 3.88%~6.89%, and the remainder is Fe. Orthogonal experimental design is used to select the optimal welding powder composition.

[0009] A method for connecting Al-Si coated hot-formed steel based on laser cladding technology is prepared according to the following steps: selecting spherical powders of C, Si, Mn, Cr, Mo, B, Ni and Fe with a particle size of 50-150 μm and a purity of ≥99.5%, using an electronic balance to accurately weigh the mass of each element, and then putting them into a powder mixer filled with argon gas, the speed of the powder mixer is 70 rad / min, and the powder mixing time is 5 hours; putting the mixed powder into a drying oven at 200°C for drying for 2 hours; putting the dried powder into a coaxial powder feeder, and blowing the mixed powder to the Al-Si coated hot-formed steel plate to be welded through the coaxial powder feeder to weld it.

[0010] A method for connecting Al-Si coated hot-formed steel based on laser cladding technology, the specific steps are as follows:

[0011] S1. Steel plate preparation before welding: The steel plate to be welded is a 1.5mm thick Al-Si coated hot-formed steel plate, which is fixed to the welding workbench with a clamp;

[0012] S2. Reserved butt gap and groove: reserve gap or groove according to the two Al-Si coated hot-formed steel plates to be welded.

[0013] S3. Set the parameters of the laser cladding equipment: set the defocus amount, laser power, laser scanning speed, spot diameter, shielding gas flow rate, powder feeding speed and other parameters of the cladding equipment.

[0014] S4. Welding: Set the laser cladding equipment parameters and procedures, and use laser cladding instead of laser wire welding to weld the Al-Si coated hot-formed steel plate.

[0015] The present invention adopts laser cladding technology to weld Al-Si coated hot-formed steel to prepare a weld with high tensile strength and high hardness, and the process operability and economic practicality are greatly improved, so that a connection method of Al-Si coated hot-formed steel based on laser cladding technology using powder instead of welding wire is promoted and applied.

[0016] Beneficial effects of the present invention:

[0017] (1) The present invention uses laser cladding technology to weld Al-Si coated hot-formed steel, using powder instead of welding wire, which has lower replacement cost, more convenient experiment, more diverse design components, and more uniform and fine grain structure of the weld and heat-affected zone.

[0018] (2) The weld after welding is full, the macroscopic morphology is smooth and beautiful, the dilution rate of the base material is similar to the weld width, the tensile strength, elongation and hardness match the base material itself, and the martensite content in the weld structure is much higher than that of δ-ferrite. Since the content of δ-ferrite is too low, it is not enough to affect the joint strength.

[0019] (3) The heat affected zone is small. Compared with laser wire welding, the heat input of Al-Si coated hot-formed steel is small when laser cladding technology is used to weld the Al-Si coated hot-formed steel, which greatly reduces the area of ​​the heat affected zone. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the metallographic microstructure of the weld center of Example 1 of the present invention.

[0021] Figure 2 This is the metallographic microstructure of the heat affected zone of Example 1 of the present invention.

[0022] Figure 3 This is the metallographic microstructure of the weld center of Example 9 of the present invention.

[0023] Figure 4 This is the metallographic microstructure of the heat affected zone of Example 9 of the present invention.

[0024] Figure 5 These are tensile test diagrams of Examples 1 and 9 of the present invention. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described below in conjunction with specific embodiments. The specifications of the selected metal powders are shown in Table 1:

[0026] Table 1 Metal powder specifications Powder Name Powder shape Powder diameter (μm) purity C spherical 53~150 ≥99.5 Si spherical 53~150 ≥99.5 Mn spherical 53~150 ≥99.5 Cr spherical 53~150 ≥99.5 Mo spherical 53~150 ≥99.5 B spherical 53~150 ≥99.5 Ni spherical 53~150 ≥99.5 Fe spherical 53~150 ≥99.5

[0027] 1.5mm thick Al-Si coated hot-formed steel was used as the base material for welding. Before welding, a grinder and 200# and 400# sandpaper were used to grind a V-shaped groove with an angle of 60° and a blunt edge of 0.5mm on the edge of the weldment. The surface was cleaned and dried with alcohol and acetone solution. The specific chemical composition (mass fraction, %) of Al-Si coated hot-formed steel is shown in Table 2:

[0028] Table 2 Composition of Al-Si coated hot-formed steel C Si Mn P S Al B Fe 0.31 0.26 1.21 0.012 0.001 0.320 0.003 margin

[0029] The specific implementation is as follows:

[0030] Implementation Case 1

[0031] 1. According to the mass percentage of each powder, use an electronic balance to accurately weigh the mass of each powder, where C: 0.06%, Si: 0.29%, Mn: 1.60%, Cr: 0.27%, Mo: 0.39%, B: 0.0029%, Ni: 5.29%, and the remainder is Fe.

[0032] 2. Put the weighed alloy powder into a powder mixer filled with argon gas, the speed of the powder mixer is 70rad / min, and the mixing time is 5h; put the mixed powder into a drying oven at 200℃ and dry it for 2h; put the dried powder into a coaxial powder feeder.

[0033] 3. Use a grinder to grind the surface to be welded, and grind out a V-shaped groove with an angle of 45° and a blunt edge of 0.5mm.

[0034] 4. Use 200#, 400#, and 600# sandpaper to grind the Al-Si coated hot-formed steel surface to be welded until the surface is smooth and tidy, and then use acetone and alcohol to clean the grinded surface respectively to remove impurities and oxide layer.

[0035] 5. Use a fixture to fix the Al-Si coated hot-formed steel to be welded on the workbench. Use a fiber laser for welding, and the specific process parameters are: laser power is 2000W, spot diameter is 4mm, scanning speed is 8mm / s, defocus is 6mm, 99.5% argon is used as the protective gas, and the gas flow rate is 10L / min.

[0036] 6. Use wire cutting to prepare samples of the welded Al-Si coated hot-formed steel plates; use a YTH-5-12 resistance heating furnace to heat treat the samples, with a holding temperature of 930°C for 3 minutes and a die cooling method.

[0037] 7. Use WDW-100E electronic universal testing machine to carry out tensile test on the specimen.

[0038] Implementation Case 2

[0039] 1. According to the mass percentage of each powder, use an electronic balance to accurately weigh the mass of each powder, where C: 0.06%, Si: 0.29%, Mn: 1.60%, Cr: 0.27%, Mo: 0.39%, Ni: 5.29%, and the remainder is Fe.

[0040] 2. Put the weighed alloy powder into a powder mixer filled with argon gas, with a speed of 70 rad / min and a mixing time of 5 hours; put the mixed powder into a drying oven at 200°C and dry it for 2 hours; put the dried powder into a coaxial powder feeder.

[0041] 3. Use a grinder to grind the surface to be welded, and grind out a V-shaped groove with an angle of 45° and a blunt edge of 0.5mm.

[0042] 4. Use 200#, 400#, and 600# sandpaper to grind the Al-Si coated hot-formed steel surface to be welded until the surface is smooth and tidy, and then use acetone and alcohol to clean the grinded surface respectively to remove impurities and oxide layer.

[0043] 5. Use a fixture to fix the Al-Si coated hot-formed steel to be welded on the workbench. Use a fiber laser for welding, and the specific process parameters are: laser power is 2000W, spot diameter is 4mm, scanning speed is 8mm / s, defocus is 6mm, 99.5% argon is used as the protective gas, and the gas flow rate is 10L / min.

[0044] 6. Use wire cutting to prepare samples of the welded Al-Si coated hot-formed steel plates; use a YTH-5-12 resistance heating furnace to heat treat the samples, with a holding temperature of 930°C for 3 minutes and a die cooling method.

[0045] 7. Use WDW-100E electronic universal testing machine to carry out tensile test on the specimen.

[0046] Implementation Case 3

[0047] 1. According to the mass percentage of each powder, use an electronic balance to accurately weigh the mass of each powder, including C: 0.11%, Si: 0.51%, Mn: 1.86%, Cr: 1.49%, Mo: 1.69%, Ni: 9.19%, Cu: 0.87%, and the remainder is Fe.

[0048] 2. Put the weighed alloy powder into a powder mixer filled with argon gas, with a speed of 70 rad / min and a mixing time of 5 hours; put the mixed powder into a drying oven at 200°C and dry it for 2 hours; put the dried powder into a coaxial powder feeder.

[0049] 3. Use a grinder to grind the surface to be welded, and grind out a V-shaped groove with an angle of 45° and a blunt edge of 0.5mm.

[0050] 4. Use 200#, 400#, and 600# sandpaper to grind the Al-Si coated hot-formed steel surface to be welded until the surface is smooth and tidy, and then use acetone and alcohol to clean the grinded surface respectively to remove impurities and oxide layer.

[0051] 5. Use a fixture to fix the Al-Si coated hot-formed steel to be welded on the workbench. Use a fiber laser for welding, and the specific process parameters are: laser power is 2000W, spot diameter is 4mm, scanning speed is 8mm / s, defocus is 6mm, 99.5% argon is used as the protective gas, and the gas flow rate is 10L / min.

[0052] 6. Use wire cutting to prepare samples of the welded Al-Si coated hot-formed steel plates; use a YTH-5-12 resistance heating furnace to heat treat the samples, with a holding temperature of 930°C for 3 minutes and a die cooling method.

[0053] 7. Use WDW-100E electronic universal testing machine to carry out tensile test on the specimen.

[0054] Implementation Case 4

[0055] 1. According to the mass percentage of each powder, use an electronic balance to accurately weigh the mass of each powder, where C: 0.06%, Si: 0.53%, Mn: 1.45%, Cr: 0.23%, Mo: 0.29%, B: 0.0031%, Ni: 4.11%, and the remainder is Fe.

[0056] 2. Put the weighed alloy powder into a powder mixer filled with argon gas, with a speed of 70 rad / min and a mixing time of 5 hours; put the mixed powder into a drying oven at 200°C and dry it for 2 hours; put the dried powder into a coaxial powder feeder.

[0057] 3. Use a grinder to grind the surface to be welded, and grind out a V-shaped groove with an angle of 45° and a blunt edge of 0.5mm.

[0058] 4. Use 200#, 400#, and 600# sandpaper to grind the Al-Si coated hot-formed steel surface to be welded until the surface is smooth and tidy, and then use acetone and alcohol to clean the grinded surface respectively to remove impurities and oxide layer.

[0059] 5. Use a fixture to fix the Al-Si coated hot-formed steel to be welded on the workbench. Use a fiber laser for welding, and the specific process parameters are: laser power is 2000W, spot diameter is 4mm, scanning speed is 8mm / s, defocus is 6mm, 99.5% argon is used as the protective gas, and the gas flow rate is 10L / min.

[0060] 6. Use wire cutting to prepare samples of the welded Al-Si coated hot-formed steel plates; use a YTH-5-12 resistance heating furnace to heat treat the samples, with a holding temperature of 930°C for 3 minutes and a die cooling method.

[0061] 7. Use WDW-100E electronic universal testing machine to carry out tensile test on the specimen.

[0062] Implementation Case 5

[0063] 1. According to the mass percentage of each powder, use an electronic balance to accurately weigh the mass of each powder, where C: 0.18%, Si: 0.21%, Mn: 1.71%, Cr: 1.25%, Mo: 1.23%, B: 0.0021%, Ni: 5.43%, and the remainder is Fe.

[0064] 2. Put the weighed alloy powder into a powder mixer filled with argon gas, with a speed of 70 rad / min and a mixing time of 5 hours; put the mixed powder into a drying oven at 200°C and dry it for 2 hours; put the dried powder into a coaxial powder feeder.

[0065] 3. Use a grinder to grind the surface to be welded, and grind out a V-shaped groove with an angle of 45° and a blunt edge of 0.5mm.

[0066] 4. Use 200#, 400#, and 600# sandpaper to grind the Al-Si coated hot-formed steel surface to be welded until the surface is smooth and tidy, and then use acetone and alcohol to clean the grinded surface respectively to remove impurities and oxide layer.

[0067] 5. Use a fixture to fix the Al-Si coated hot-formed steel to be welded on the workbench. Use a fiber laser for welding, and the specific process parameters are: laser power is 2000W, spot diameter is 4mm, scanning speed is 8mm / s, defocus is 6mm, 99.5% argon is used as the protective gas, and the gas flow rate is 10L / min.

[0068] 6. Use wire cutting to prepare samples of the welded Al-Si coated hot-formed steel plates; use a YTH-5-12 resistance heating furnace to heat treat the samples, with a holding temperature of 930°C for 3 minutes and a die cooling method.

[0069] 7. Use WDW-100E electronic universal testing machine to carry out tensile test on the specimen.

[0070] Implementation Case 6

[0071] 1. According to the mass percentage of each powder, use an electronic balance to accurately weigh the mass of each powder, where C: 0.06%, Si: 0.29%, Mn: 1.60%, Cr: 0.27%, Mo: 0.39%, B: 0.0029%, Ni: 5.29%, and the remainder is Fe.

[0072] 2. Put the weighed alloy powder into a powder mixer filled with argon gas, with a speed of 70 rad / min and a mixing time of 5 hours; put the mixed powder into a drying oven at 200°C and dry it for 2 hours; put the dried powder into a coaxial powder feeder.

[0073] 3. Use 200#, 400#, and 600# sandpaper to grind the Al-Si coated hot-formed steel surface to be welded until the surface is smooth and tidy, and then use acetone and alcohol to clean the grinded surface respectively to remove impurities and oxide layer.

[0074] 4. Use a fixture to fix the Al-Si coated hot-formed steel to be welded on the workbench. Use a fiber laser for welding, and the specific process parameters are: laser power is 2000W, spot diameter is 4mm, scanning speed is 8mm / s, defocus is 6mm, 99.5% argon is used as the protective gas, and the gas flow rate is 10L / min.

[0075] 5. Use wire cutting to prepare samples of the welded Al-Si coated hot-formed steel plates; use a YTH-5-12 resistance heating furnace to heat treat the samples, with a holding temperature of 930°C for 3 minutes and a die cooling method.

[0076] 6. Use WDW-100E electronic universal testing machine to perform tensile test on the specimen.

[0077] Implementation Case 7

[0078] 1. According to the mass percentage of each powder, use an electronic balance to accurately weigh the mass of each powder, where C: 0.06%, Si: 0.29%, Mn: 1.60%, Cr: 0.27%, Mo: 0.39%, B: 0.0029%, Ni: 5.29%, and the remainder is Fe.

[0079] 2. Put the weighed alloy powder into a powder mixer filled with argon gas, with a speed of 70 rad / min and a mixing time of 5 hours; put the mixed powder into a drying oven at 200°C and dry it for 2 hours; put the dried powder into a coaxial powder feeder.

[0080] 3. Use 200#, 400#, and 600# sandpaper to grind the Al-Si coated hot-formed steel surface to be welded until the surface is smooth and tidy, and then use acetone and alcohol to clean the grinded surface respectively to remove impurities and oxide layer.

[0081] 4. Use a fixture to fix the Al-Si coated hot-formed steel to be welded on the workbench, and reserve a gap of 0.4mm between the steel plates to be welded. Use a fiber laser for welding, and the specific process parameters are: laser power of 2000W, spot diameter of 4mm, scanning speed of 8mm / s, defocus of 6mm, 99.5% argon as the protective gas, and gas flow of 10L / min.

[0082] 5. Use wire cutting to prepare samples of the welded Al-Si coated hot-formed steel plates; use a YTH-5-12 resistance heating furnace to heat treat the samples, with a holding temperature of 930°C for 3 minutes and a die cooling method.

[0083] 6. Use WDW-100E electronic universal testing machine to perform tensile test on the specimen.

[0084] Example 8

[0085] 1. According to the mass percentage of each powder, use an electronic balance to accurately weigh the mass of each powder, where C: 0.06%, Si: 0.29%, Mn: 1.60%, Cr: 0.27%, Mo: 0.39%, B: 0.0029%, Ni: 5.29%, and the remainder is Fe.

[0086] 2. Put the weighed alloy powder into a powder mixer filled with argon gas, with a speed of 70 rad / min and a mixing time of 5 hours; put the mixed powder into a drying oven at 200°C and dry it for 2 hours; put the dried powder into a coaxial powder feeder.

[0087] 3. Use wire cutting to prepare samples of unwelded Al-Si coated hot-formed steel plates; use a YTH-5-12 resistance heating furnace to heat treat the samples, with a holding temperature of 930°C for 3 minutes and a cooling method of die cooling.

[0088] 4. Use WDW-100E electronic universal testing machine to perform tensile test on the specimen.

[0089] Implementation Case 9

[0090] 1. Al-Si coated hot-formed steel is welded by laser wire welding, wherein the welding wire composition mass percentage is: C: 0.06, Si: 0.29, Mn: 1.60, Cr: 0.27, Mo: 0.39, B: 0.0029, Ni: 5.29, and the balance is Fe.

[0091] 2. Use a grinder to grind the surface to be welded, and grind out a V-shaped groove with an angle of 45° and a blunt edge of 0.5mm.

[0092] 3. Use 200#, 400#, and 600# sandpaper to grind the Al-Si coated hot-formed steel surface to be welded until the surface is smooth and tidy, and then use acetone and alcohol to clean the grinded surface respectively to remove impurities and oxide layer.

[0093] 4. The Al-Si coated hot-formed steel is welded by laser wire-filling welding process. The welding gun and wire-feeding mechanism are located above the steel plate to be welded. The welding gun and wire-feeding mechanism are fed simultaneously to ensure the normal operation of the wire feeding system. The welding gun angle is adjusted so that the welding wire forms an inclination angle of 30° with the welding direction.

[0094] 5. Use wire cutting to prepare samples of the welded Al-Si coated hot-formed steel plates; use a YTH-5-12 resistance heating furnace to heat treat the samples, with a holding temperature of 930°C for 3 minutes and a die cooling method.

[0095] 6. Use WDW-100E electronic universal testing machine to perform tensile test on the specimen.

[0096] Table 3 Powder and welding wire composition ratios of Examples 1 to 9 project C Si Mn Cr Mo B Ni Cu Fe Reserved gap / mm Pokou Filling material form Example 1 0.06 0.29 1.60 0.27 0.39 0.0029 5.29 0 margin 0 V-shaped groove with an angle of 45° and a blunt edge of 0.5 mm powder Example 2 0.06 0.29 1.60 0.27 0.39 0 5.29 0 margin 0 V-shaped groove with an angle of 45° and a blunt edge of 0.5 mm powder Example 3 0.11 0.51 1.86 1.49 1.69 0 9.19 0.87 margin 0 V-shaped groove with an angle of 45° and a blunt edge of 0.5 mm powder Example 4 0.06 0.53 1.45 0.23 0.29 0.0031 4.11 0 margin 0 V-shaped groove with an angle of 45° and a blunt edge of 0.5 mm powder Example 5 0.18 0.21 1.71 1.25 1.23 0.0021 5.43 0 margin 0 V-shaped groove with an angle of 45° and a blunt edge of 0.5 mm powder Example 6 0.06 0.29 1.60 0.27 0.39 0.0029 5.29 0 margin 0 none powder Example 7 0.06 0.29 1.60 0.27 0.39 0.0029 5.29 0 margin 0.4 none powder Example 8 Example 9 0.06 0.29 1.60 0.27 0.39 0.0029 5.29 0 margin 0 V-shaped groove with an angle of 45° and a blunt edge of 0.5 mm Welding wire .

[0097] Performance Testing

[0098] Test method for tensile strength and elongation of welded joints: Cut standard tensile specimens from welded parts to ensure that the size and shape of the specimens meet the requirements of relevant standards. The weld area of ​​the specimen should be located in the middle of the tensile specimen. Mark the standard gauge length of 25 mm on the parallel section of the specimen. Install the specimen in the fixture of the universal testing machine to ensure that the specimen is centered and avoid eccentric loading. Start the testing machine and load the specimen at a constant tensile speed of 1 mm / min until the specimen breaks.

[0099] Table 4 is the experimental data of the embodiment project Tensile strength / MPa Joint elongation / % Unwelded parent metal specimen 2000 9.0 Example 1 2023 9.4 Example 2 1658 7.3 Example 3 2011 6.7 Example 4 1637 8.8 Example 5 2041 6.8 Example 6 1566 6.8 Example 7 1987 8.9 Example 8 2000 9.0 Example 9 2033 9.5

[0100] Combining Example 1 and Example 2, it can be seen that the tensile strength and joint elongation of the weld prepared in Example 1 are greater than those of the weld prepared in Example 2, mainly because a trace amount of boron is added to the powder of Example 1, which makes the hardenability of the weld doubled compared with that of Example 2. Boron dissolves in the solid solution, the lattice becomes larger, and the boron in the grain boundary has the effect of preventing recrystallization diffusion, so that the strength of the weld is improved.

[0101] Combining Example 1 and Example 3, it can be seen that the tensile strength prepared by the two groups of experiments is not much different, and the joint elongation of Example 3 is lower than that of Example 1, mainly because Example 3 adds higher content of Ni, Cr, Mo, and Cu elements to replace the B element in Example 1 to improve the hardenability of the weld, so that there is no obvious difference in the strength of the joints between the two. However, due to the addition of a large content of Cu elements and a high carbon equivalent, the plasticity at the weld is significantly reduced, and the elongation is significantly lower than that of Example 1.

[0102] Combining Example 1 with Example 4 and Example 5, it can be seen that the tensile strength of Example 4 is much lower than that of Example 1, and the joint elongation is slightly lower than that of Example 1. The tensile strength of Example 5 is not significantly different from that of Example 1, and the joint elongation is much lower than that of Example 1. This is because the carbon equivalent of Example 4 is lower, and the carbon equivalent of Example 5 is higher, resulting in low strength at the weld of Example 4, high plasticity and toughness, while Example 5 is the opposite, with high strength at the weld, low plasticity and toughness. The higher the carbon equivalent, the higher the strength of the steel, but the worse its plasticity and toughness.

[0103] Combining Example 1, Example 6 and Example 7, there is no obvious difference in the tensile strength and joint elongation between Example 1 and Example 7, and both are greater than the tensile strength and joint elongation of Example 6. This is because Example 6 has neither a reserved groove nor a reserved gap, resulting in failure to achieve complete penetration.

[0104] Combining the unwelded parent materials of Example 1, Example 9 and Example 8, the tensile strength of the unwelded parent material in Example 8 is 2000 MPa and the elongation is 9.0%, as shown in Tables 4 and Figure 5 As shown in the figure, the tensile strength and joint elongation of Example 1 and Example 9 are both matched with those of the unwelded parent metal samples, indicating that the microstructure and properties of the weld are comparable to or even slightly higher than those of the parent metal itself, and the welded joint has good tensile properties and elongation. Figure 1 , Figure 2 As shown, the metallographic microstructure of the weld and heat-affected zone of Example 9 is as follows Figure 1 , Figure 2As shown, comparative analysis shows that the microstructures at the weld joints of the two are martensite and δ-ferrite. The δ-ferrite microstructure at the center of the weld in Example 1 is skeletal, and the heat-affected zone is blocky. Compared with Example 9, the δ-ferrite is less distributed and the grain size is smaller. This is mainly because when welding with welding wire, the Al element is enriched in the heat-affected zone near the weld fusion line due to the Marangoni convection, which makes the δ-ferrite distributed more in the heat-affected zone and larger in size. The use of powder for welding can effectively reduce the phenomenon of poor performance of the welding heat-affected zone caused by convection through rapid cooling and adjustment of parameters such as defocusing through additive manufacturing technology.

[0105] In summary, Example 1 is the best combination of components and processes, and its tensile strength and elongation are better than those of the other components and process designs, and match the samples of the unwelded parent material and the test group using welding wire. The present invention uses powder for welding, while retaining the original advantages of laser wire welding, reduces the heat affected zone, refines the grains through rapid cooling and solidification, and reduces the cost of component adjustment.

[0106] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for connecting Al-Si coated hot-formed steel based on laser cladding technology, characterized in that: This method uses a high-energy laser beam to melt the material and weld the parent material to form a high-quality weld. Laser cladding technology is used to connect aluminum-silicon coated hot-formed steel plates, realizing the concept of replacing welding wire with powder. Compared with welding wire, it has the advantages of lower powder replacement cost, fine equiaxed grain structure of weld, smaller heat-affected zone, more convenient experiment, and more diverse design components.

2. According to claim 1, a laser cladding high-hardness, high-wear-resistant high-entropy alloy coating and a preparation method thereof are characterized in that: Follow these steps to prepare: a. Select spherical powders of C, Si, Mn, Cr, Mo, B, Ni, and Fe with a particle size of 50-150μm and a purity of ≥99.5%, accurately weigh the mass of each element, and then put them into a powder mixer filled with argon gas. The speed of the powder mixer is 70rad / min, and the mixing time is 5h; the mixed powder is placed in a drying oven at 200℃ for 2h; the dried powder is placed in a coaxial powder feeder through the coaxial powder feeder; b. Use Al-Si coated hot-formed steel as the base material, polish the steel surface smooth before welding, and clean the surface with alcohol solution and acetone solution; c. The mixed powder is blown to the Al-Si coated hot-formed steel to be welded through a coaxial powder feeder to form a weld; process parameters: laser power is 2000W, spot diameter is 4mm, scanning speed is 8mm / s, defocus is 6mm, 99.5% argon is used as the protective gas, and the gas flow rate is 10L / min.